Herding Behavior in Prediction Markets: Evidence from UK Financial Spread-Trading Markets - Chung-Ching Tai; Sarist Gulthawatvichai; Ming-Chien Sung; Johnnie E. V. Johnson; Jeremy Eng-Tuck Cheah (My University, 2023)
We contrast the degree (strong vs. weak), nature (interaction between more and less informed traders; MI and LI, respectively), and patterns of herding behavior (via their feedback strategies) among MI and LI traders and their speed of reaction to shifts in trading by these groups. This is achieved by analyzing individual investment records of 1,943 traders in UK spread-trading markets (2010–2012). We find that herding is far more prevalent than previous studies suggest, particularly among LI; herding activities of MI and LI are related, and the means used to distinguish MI and LI needs to be considered carefully.
Keywords: Herd behavior; Investment; Trading strategy; Financial Markets and Investment Strategies